Role of Optical Coherence Tomography (OCT) in Early Detection of Subclinical Cystoid Macular Edema after Nd-YAG Laser Capsulotomy: Doi: 10.36351/pjo.v37i1.1143 - Shaikh, Muhammad Adnan; Dareshani, Shela; Faiz-ur-Rab, Khowaja; Saleem, Tariq; Ali, Mazhar (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine role of optical coherence tomography (OCT) in early detection of subclinical cystoid macular edema (CME) after Nd-YAG laser capsulotomy in patients with posterior capsular opacification (PCO). Study Design: Descriptive case-series. Place and Duration of Study: Department of Ophthalmology Unit 1, Dow University of Health Sciences and Civil Hospital Karachi from 1-July-2015 to 31-Dec-2015. Methods: A total of 72 eyes with unilateral or bilateral visually significant PCO following uncomplicated cataract surgery with posterior chamber intraocular lens implantation were included in the study. Patients with corneal opacities, glaucoma, retinopathy, maculopathy, optic neuropathy, complicated cataract surgery, previous ocular surgery other than cataract surgery and High refractive errors were excluded from the study. Best-corrected visual acuity (BCVA), Slit lamp examination, posterior segment examination and macular thickness was measured using spectral domain (TOPCON 3D OCT) optical coherence tomography before laser and at 1 week and at 1 month after laser. Results: Mean age was 55.76 ± 5.28 with Confidence interval of 55.02 – 56.49 years. Eighty-one were males and 122 were females. Subclinical cystoid macular edema (CME) was found in 10 (14%) patients. Out of the patients who had CME, 3 were in age group of 40-55 years and seven were in age group of 56-70 years. P value was found to be significant i.e. (P = 0.039). Conclusion: Optical coherence tomography OCT is a non invasive and useful tool for early detection and management of subclinical cystoid macular edema after Nd-YAG laser capsulotomy in patients having posterior capsular opacification (PCO). Key Words: Cystoid Macular Edema, Nd-YAG laser, Posterior Capsular Opacification. Optical Coherence Tomography (OCT).